The characterisation of the lead flotation circuit at Black Mountain Mining (Pty) Ltd. using the floatability component model approach - Galant, Malikaah (Department of Chemical Engineering, 2017)
Black Mountain Mining (Pty) Ltd. (BMM) is a base metal operation that has been producing chalcopyrite-, galena- and sphalerite-bearing concentrates for over 30 years. Silver is recovered in the concentrates as a result of elemental substitution within the crystal lattice of chalcopyrite and galena minerals. The primary objective of this study was to adapt the Floatability Component Model (FCM) as a simplified proof-of-concept model for the Lead flotation circuit of the BMM Concentrator based on plant- and laboratory-scale data. The model obtained, using the FCM approach in conjunction with the Woodburn and Wallin (1984) methodology, should give insight to the metallurgical team regarding the performance of the circuit based on the data pertaining to the feed characteristics of the Lead flotation circuit. Additionally, as a result of the known association of silver with galena minerals, an objective of the study was to be able to predict the response of silver based on the response of galena minerals. The model for the Lead flotation circuit of BMM Concentrator was developed in a single MS Excel spreadsheet and it was important that the raw data used to develop the model could be obtained easily, inexpensively and in a manner that was not disruptive to the operation.